Poskus konceptualizacija talentiranosti na športnem področju - Kukanja Gabrijelčič, Mojca; Volmut, Tadeja (Revija za elementarno izobraževanje, 2020)
Conceptualization of Talent in Sport. The purpose of this paper is to present the interdisciplinary problem of giftedness and talent in the Slovene elementary school system and attempt to meaningfully interpret the terminology of both terms for the field of sport education. Despite the considerable attention paid to researching the changing understanding of giftedness in relation to talent, talent in sports environments and the applicable value of conceptualization are still not known. One reason for this is that sports talent has not been adequately defined in the Slovenian program and legislative platforms.
Keywords: giftedness, talent, sports education, elementary school.